Invertebrate communities of Bay of Fundy salt marsh pools: comparison of a natural and recovering marsh - Noel, Paula E.; Sharma, Bidhya; Chmura, Gail L. (Frontiers in Ecology and Evolution, 2023)
Disturbed salt marshes may recover with little additional management once tidal inundation is restored. We assessed the success of such recovery by comparing the invertebrate biota of Bay of Fundy salt marsh pools in a reference site at Dipper Harbour to that of Saints Rest marsh that had been drained for over a century and to which tidal flooding had been returned 50 years prior to our study. The sediments and vegetation of salt marsh pools were sampled seasonally throughout one year. Average biomass of pool invertebrates ranged from 1.8 to 4.0 g dry wt m -2 , depending on the amount of vegetation cover in the pools. The most abundant organisms of the pools were the gastropod Ecrobia truncata (=Hydrobia tottentei), Tubificidae (=Naididae) oligochaetes, and Chironomidae (=Chironomini). We compared overall abundance and biomass of the invertebrates in the pool communities, assessing the month of sampling, pool elevation, and source marsh as explanatory variables. Our analyses revealed that marsh origin of pools seldom explained a significant amount of variance, and when it did, the proportion of variance explained was usually lower than elevation of pools and month of sampling. Diversity of invertebrates found in all pools was higher at the recovering site with species richness >40% higher than in the reference site. We conclude that after an estimated 50 years since dyke failure and return of tidal flooding to Saints Rest marsh, that the ecosystem function represented by pools and their fauna has recovered.